The Challenge of Chronic Pain Management by PM&R Specialist - Maria Regina Rachmawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
According to the definition from international association for the study of pain (IASP), pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage. Besides, there are many term of unpleasant sensory that complaint by patient as a pain, such as allodynia, hyperalgesia, and hyperesthesia. The pain is one of the most cases that came to seeking a doctor. The data from Indonesian National Health Insurance (JKN) from 2014-2017 have revealed that pain cases were the most frequent in Rehabilitation Medicine Services, i.e. low back pain, knee pain, and shoulder pain. The prevalence of pain is increasing along with ageing, sedentary life style, obesity and chronic diseases.